2010
DOI: 10.1016/j.cell.2010.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Myc-Nick: A Cytoplasmic Cleavage Product of Myc that Promotes α-Tubulin Acetylation and Cell Differentiation

Abstract: The Myc oncoprotein family comprises transcription factors that control multiple cellular functions and are widely involved in oncogenesis. Here we report the identification of Myc-nick, a cytoplasmic form of Myc generated by calpain- dependent proteolysis at lysine 298 of full-length Myc. Myc-nick retains conserved Myc Box regions but lacks nuclear localization signals and the bHLHZ domain essential for heterodimerization with Max and DNA binding. Myc-nick induces α-tubulin acetylation and altered cell morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
214
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(229 citation statements)
references
References 50 publications
12
214
2
1
Order By: Relevance
“…Although a previous report showed that the Myc protein level increases in the nucleus upon H. pylori infection in a mouse macrophage cell line (21), our finding is consistent with several other studies showing that Myc localizes in the cytoplasm in various cells including lymphoid and differentiated myeloid cells, fibroblasts, and HeLa cells (24)(25)(26)(27). It has not been known why Myc is localized in the cytoplasm in some cells but not in the others.…”
Section: Discussionsupporting
confidence: 82%
“…Although a previous report showed that the Myc protein level increases in the nucleus upon H. pylori infection in a mouse macrophage cell line (21), our finding is consistent with several other studies showing that Myc localizes in the cytoplasm in various cells including lymphoid and differentiated myeloid cells, fibroblasts, and HeLa cells (24)(25)(26)(27). It has not been known why Myc is localized in the cytoplasm in some cells but not in the others.…”
Section: Discussionsupporting
confidence: 82%
“…The recent study indicated that stress can induce the production of an Myc-nick (short form of c-Myc), which promoted cell survival and autophagy. 33,34 Our data indeed showed that Myc-nick was easily detected when cells were cultured at dense condition (Supplementary Figure S3C). However, Myc-nick cannot bind to (Supplementary Figure S3B) and be degraded by REGγ (Supplementary Figure S3C).…”
Section: Resultsmentioning
confidence: 52%
“…14) and GCN5 (ref. 16). The lack of detectable K40 a-tubulin acetylation in aTAT1 À / À mice reported here indicates that these other enzymes are not able to rescue deficiency of aTAT1, and therefore probably do not acetylate a-tubulin directly in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…14), San 15 , GCN5 (ref. 16) and aTAT1 (refs 9,17,18). Of these, compelling evidence supports a role for aTAT1 as the major a-tubulin acetyltransferase in Tetrahymena and C. elegans 9,17 .…”
mentioning
confidence: 99%